Review of Perspectives of Programming Olympiads in Kazakhstan - Syzdykov, Mirzakhmet (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
We present the research aimed at the current status of the programming Olympiads in which Kazakhstan is involved and holds a positive line, we propose various pros and cons for the training of the participants of these events. Since the participation of Kazakhstan in the International Olympiad in Informatics (IOI) for schoolers and International Collegiate Programming Contest (ICPC), which is upheld by Association of Computing Machinery (ACM), most of the better results were shown on IOI rather than ACM ICPC, where still participants from our country demonstrate stable tendency at gaining finals, however, still not receiving the prize pool consisting of the first twelve teams in the final rating. The problem which is to be solved by participants can be also classified as polynomial (P-complete) or non-polynomial (NP-complete), which, in turn, gives us the observation of what could be solved using rational solution. We demonstrate this fact on examples of two problems from ACM ICPC.